الحديث : استعمالات خاصة للقرآن الكريم لبعض المفردات - Toure. A.K.; Ismail,M.Y.; Mohamed Amin,M.G.; Al-Hukam.; Mohamed Ghazalin. LLC; Mohammed @ Matt. A.; David Noor.M.Z.; Muhammad Qassem. A. (Universiti Sains Islam Malaysia, 2024)
This study aims to highlight some of the use of the Quran certain Arabic words known in a different meaning which does not change the original meaning but adds new meaning suitable with the story or topic which increases the beauty of the eloquence of the Qur'an. The study also highlights the accuracy in which the Qur'an select its words which gives a clear picture to the reader. The study also highlights the unique style of Coran in using some known common worlds for all types of some category of things to a specific and solely use. The researchers adopted the inductive method in interpretation and analysis of the chosen verses and elaborate in their study. The most important findings of the study are that the meanings and interpretation of the Qur'an is continuous for the successive generations, it is tender and inexhaustible for scholars capable to interpret it base.